Rhodococcus equi, an Unusual Human Pathogen That Causes Cavitating Pneumonia in Patients With AIDS - J. Vandersnickt; Pee J. Van; S. Vandamme; C. Kenyon; E. Florence; S. Van Ierssel; E. Vlieghe; C. Theunissen (Case Reports in Infectious Diseases, 2024)
Rhodococcus equi is a rare human opportunistic pathogen that has been increasingly reported in recent decades. It mainly affects immunosuppressed patients, and in particular human immunodeficiency virus (HIV)–infected patients, where it typically presents as cavitary pneumonia. Early treatment with combined and effective antimicrobials and antiretroviral therapy after prompt diagnosis is essential to ensure an optimal outcome. We present a case series of three human Rhodococcus equi infections in HIV-infected patients with advanced immune suppression, treated at the University Hospital of Antwerp, Belgium.